Improving Learning Outcomes with an Ethnoscience-Based Contextual Approach - Hermanto, Fery (Science Education and Application Journal, 2021)
The objective research purposed to analyze improvement of student learning outcomes using the Ethno science-based Contextual Learning Approach in the classification of living things. Research type one group pretest and posttest design. The research subjects were 36 students of class VII-A SMP Negeri 1 Maba, East Halmahera. The result showed that 1) Learning outcomes improved significance, 2) feasibility of instruction good category, and 3) he response of student’s positively. It could be concluded that the learning procces effective to improved student’s learning achievement.